Efficacy, immunogenicity and safety of HPV vaccination in Chinese population: A meta-analysis - Guo, Jianming; Guo, Shuyan; Dong, Siping (Frontiers in Public Health, 2023)
Objective To evaluate the efficacy, immunogenicity and safety of HPV vaccination in Chinese population. Methods PubMed, Embase, Web of Science and Cochrane Library from inception to November 2022 were searched to collect information on clinical trials of HPV vaccines. Database search strategy used a combination of subject terms and free terms. Studies were first identified by two authors through reading the title, abstract and full texts and, subsequently, based on the inclusion criteria: Chinese population, with at least one of the following outcomes (efficacy, immunogenicity, and safety), and HPV vaccine RCT, those eligible were included in this paper. Efficacy, immunogenicity and safety data, pooled by random effects models, are presented as risk ratios [95% confidence intervals (CI)]. Results Eleven RCTs and four follow-up studies were included. Meta-analysis showed that HPV vaccine had good profile of efficacy and immunogenicity. The seroconversion rates were significantly higher among the vaccinated, uninfected (initial negative serum antibody) population than the placebo population for both HPV-16 (RR 29.10; 95% CI: 8.40–100.82) and HPV-18 (RR 24.15; 95% CI: 3.82–152.84), respectively. A significant reduction of the incidence of cervical intraepithelial neoplasia grade 1 (CIN1+) (RR 0.05; 95% CI: 0.01–0.23) and CIN2+ (RR 0.09; 95% CI: 0.02–0.40) was also measured. Risk for serious adverse events after HPV vaccination indicated comparable outcomes between vaccination and placebo. Conclusions For Chinese populations, HPV vaccines enhance the level of HPV16- and HPV18-specific antibodies and reduce the incidence of CIN1+ and CIN2+ in uninfected population. Also, the risk of serious adverse events in both groups are almost equivalent. More data are needed to establish vaccine efficacy with cervical cancer.